2021
DOI: 10.1002/cphc.202100725
|View full text |Cite
|
Sign up to set email alerts
|

Insulating Polymers as Additives to Bulk‐Heterojunction Organic Solar Cells: The Effect of Miscibility

Abstract: Adding insulating polymers to conjugated polymers is an efficient strategy to tailor their mechanical properties for flexible organic electronics. In this work, we selected two insulating polymers as additives for high‐performance photoactive layers and investigated the mechanical and photovoltaic properties in organic solar cells (OSCs). The insulating polymers were found to reduce the electron mobilities in the photoactive layers, and hence the power conversion efficiencies were significantly decreased. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Moreover, large SBS aggregates could negatively affect the crack onset strain through interface adhesions. Inferior interfaces between the SY matrix and large SBS aggregates would generate more cavities, leading to an easier generation of the cracks . Both the COS and Young’s modulus measurements indicated that the stretchability of the SY film was improved by blending SBS up to 25%.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, large SBS aggregates could negatively affect the crack onset strain through interface adhesions. Inferior interfaces between the SY matrix and large SBS aggregates would generate more cavities, leading to an easier generation of the cracks . Both the COS and Young’s modulus measurements indicated that the stretchability of the SY film was improved by blending SBS up to 25%.…”
Section: Resultsmentioning
confidence: 99%
“…[ 3a ] However, the addition of elastomers often induced the strong phase separation of elastomer domains from the active domains and deteriorated the charge generation and transport properties of the PSCs. [ 3a,7 ] For instance, introducing 30 wt.% of the SEBS elastomers into the PM6:N3 system drastically increased the domain size of blends from 17 to 242 nm and reduced the PCE of the PSCs from 15.4 to 11.3%. [ 3a ] Therefore, molecular design for preventing strong phase separation between the elastomers and conjugated polymers should be developed for enhancing the stretchability of the blend films without compromising the PCEs of the PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been used to improve their mechanical properties, including physically mixed insulating polymers (PS, PDMS, SEBS, etc. ), covalently linked insulating polymer chains into the backbones or side chains, ternary OSCs by using the third conjugated components, and adjusting the amorphous/crystalline nature. These methods can indeed help to improve the COS, but there are still some issues. For example, the addition of insulating polymers will dilute the conjugated components, and the enhancement of the amorphous region will lower charge carrier mobilities and PCEs in OSCs. , It will be an important task to develop conjugated polymers with excellent mechanical properties and meanwhile provide high performance in OSCs.…”
Section: Introductionmentioning
confidence: 99%